Wall conditioning discharges driven by Т-shaped antenna in Uragan-2M - Lozin, A.V.; Kozulia, M.M.; Korovin, V.B.; Beletskii, A.A.; Glazunov, G.P.; Konotopskiy, A.L.; Baron, D.I.; Moiseenko, V.E.; Grigor’eva, L.I.; Chechkin, V.V.; Shapoval, A.N.; Makhov, M.M.; et al. (Вопросы атомной науки и техники, 2018)
New VHF antenna was introduced at Uragan-2M for VHF vacuum chamber wall conditioning without and with
weak magnetic field. It was made as a T-shaped ¼ wavelength double rod. The T-shaped antenna is capable for slow
waves generation due to its longitudinal currents. This new wall conditioning tool was studied analyzing vacuum
chamber wall conditions and achieved plasma parameters. Для чистки вакуумної камери Урагану-2М у слабкому магнітному полі і без магнітного поля було
впроваджено нову СВЧ-антену. Її було виконано у вигляді чвертьхвильового стрижня. Т-подібна антена
здатна створювати повільні хвилі з повздовжніми струмами. Новий інструмент для чистки стінок вивчався
через стан вакуумної камери і досягнутих параметрів плазми. Для чистки вакуумной камеры Урагана-2М в слабом магнитном поле и без магнитного поля была
внедрена новая СВЧ-антенна. Она была выполнена в виде четвертьволнового стержня. Т-образная антенна
способна создавать медленные волны с продольными токами. Новый инструмент для чистки стенок
изучался посредством состояния вакуумной камеры и достигнутых параметров плазмы.